Dynamic analysis of composite beam with piezoelectric layers under thermo-mechanical load - Toudehdehghan A.; Rahman M.M.; Nagi F. (Institute of Physics Publishing, 2023)
Actuators; Composite beams and girders; Engineering research; Equations of motion; Finite element method; Piezoelectric actuators; Piezoelectricity; Mechanical deformation; Piezoelectric layers; Piezoelectric sensors and actuators; Sensor and actuators; Simply supported beams; Thermal environment; Thermo mechanical loads; Timoshenko's theory; Dynamic mechanical analysis